Virus infection pattern imprinted and diversified the differentiation of T-cell memory in transcription and function - Wang, Yuan; Mei, Xinyue; Lin, Zhengfang; Yang, Xiaoyun; Cao, Jinpeng; Zhong, Jiaying; Wang, Junxiang; Cheng, Li; Wang, Zhongfang (Frontiers in Immunology, 2024)
Introduction Memory T (Tm) cells are a subpopulation of immune cells with great heterogeneity. Part of this diversity came from T cells that were primed with different viruses. Understanding the differences among different viral-specific Tms will help develop new therapeutic strategies for viral infections. Methods In this study, we compared the transcriptome of Tm cells that primed with CMV, EBV and SARS-CoV-2 with single-cell sequencing and studied the similarities and differences in terms of subpopulation composition, activation, metabolism and transcriptional regulation. Results We found that CMV is marked by plentiful cytotoxic Temra cells, while EBV is more abundant in functional Tem cells. More importantly, we found that CD28 and CTLA4 can be used as continuous indicators to interrogate the antiviral ability of T cells. Furthermore, we proposed that REL is a main regulatory factor for CMV-specific T cells producing cytokines and plays an antiviral role. Discussion Our data gives deep insight into molecular characteristics of Tm subsets from different viral infection, which is important to understand T cell immunization. Furthermore, our results provide basic background knowledges for T cell based vaccine development in future.